Differential functional von Foerster equations with renewal - Leszczyński, H. (Condensed Matter Physics, 2008)
Natural iterative methods converge to the exact solution of a differential-functional von Foerster-type equation which describes a single population dependent on its past time and state densities as well as on its total size. On the lateral boundary we impose a renewal condition.